PRACTICAL WAYS AND EXAMPLES OF PRAGMATICS - Farmanov Gayrat Khujakulovich (American Journals, 2023)
Learning English language is to cultivate English learners’ communicative competence. Since the pragmatic competence is an essential element of communicative competence, it should be important content with practice while teaching the language.
Keywords: Pragmatics, sociocultural or sociolinguistic competences communicative competence, idiomatic expression.